A Novel Data Acquisition System for Obtaining Thermal Parameters of Building Envelopes - Behnam Mobaraki; Seyedmilad Komarizadehasl; Francisco Javier Castilla Pascual; José Antonio Lozano-Galant; Rocio Porras Soriano (Buildings, 2022)
Owing to the high energy consumption in the building sector, appraising the thermal performance of building envelopes is an increasing concern. Recently, a few in situ methodologies to diagnose the thermal parameters of buildings have been considered. However, because of their limitations such as low accuracy, limited number of measurements, and the high cost of monitoring devices, researchers are seeking a new alternative. In this study, a novel hyper-efficient Arduino transmittance-meter was introduced to overcome these limitations and determine the thermal parameters of building envelopes. Unlike conventional methodologies, the proposed transmittance-meter is based on synchronized measurements of different parameters necessary to estimate the transmittance parameter. To verify the applicability of the transmittance-meter, an experimental study was conducted wherein a temperature-controlled box model was thermally monitored, and the outputs of the transmittance-meter employed were compared with those captured by a commercial device. The results revealed a high level of reduction in cost and a low range of difference compared with the latter, thereby validating the applicability of the proposed thermal monitoring system.